THE IMPLEMENTATION OF STORYTELLING LEARNING IN SPEAKING THROUGH TWO STAY TWO STRAY - Hamdani, Haris; Mawarni, Venti; Supriatna, Nana (Journal of English Education and Linguistics, 2025)
English holds significant importance for students for a multitude of reasons, impacting their academic, professional, and personal development. Numerous scholarships and international exchange programs require proficiency in English, opening doors to global educational experiences this study aims to find out the application of the Two Stay Two Stray strategy through Storytelling in the learning process, find out Two Stay Two Stray strategy through Storytelling that improve students' speaking ability, and know obstacles in implementing Two Stay Two Stray strategy through Storytelling. This research uses qualitative methods with descriptive explanations. The results of this study found that the teachers are successful in implementing storytelling learning in speaking through the Two Stay Two Stray strategy. The obstacles which are faced by the teachers are 1) students have various characteristics, 2) students have low vocabularies, and so on. Meanwhile, the opportunities that are faced by the teachers are 1) the dynamic nature of Two Stay Two Stray keeps students actively engaged, 2) regular practice in speaking and presenting stories builds students’ confidence, and so forth. The English teachers’ interviews show that the teachers succeed in implementing storytelling learning in speaking through Two Stay Two Stray. Besides, the students’ interviews show that the students can enhance their speaking skills in storytelling learning through the Two Stay Two Stray strategy.